Impact of Private Real Estate Promotion on Urban Sprawl and Tourism Development in Skikda - Assia, Lifa; Nahla, Daoued (Future Science, 2024)
Urban planning in Algeria, manifested through its two main urban planning instruments, the PDAU (Urban Development Master Plan) and the POS (Land Use Plan), has accompanied a remarkable acceleration of urbanization in Algerian cities. This article focuses on private real estate development and its impacts on newly urbanized spaces and the mechanisms of their production within the coastal city of Skikda. It is evident that urban sprawl in this city has occurred based on land availability, in a competition for high-value tourist lands, wita Urban planning in Algeria, manifested through its two main urban planning instruments, the PDAU (Urban Development Master Plan) and the POS (Land Use Plan), has accompanied a remarkable acceleration of urbanization in Algerian cities. This article focuses on private real estate development and its impacts on newly urbanized spaces and the mechanisms of their production within the coastal city of Skikda. It is evident that urban sprawl in this city has occurred based on land availability, in a competition for high-value tourist lands, with regularization achieved through urban planning instruments. This has led to excessive consumption of prime sites for housing production, driven by a dynamic of land speculation. Through the analysis of the modalities of manufacturing newly urbanized spaces and an opportunity for tourism development and attractiveness in Skikda. h regularization achieved through urban planning instruments. This has led to excessive consumption of prime sites for housing production, driven by a dynamic of land speculation. Through the analysis of the modalities of manufacturing newly urbanized spaces and an opportunity for tourism development and attractiveness in Skikda